Variability in storm season intensity modulates ocean acidification conditions in the northern Strait of Georgia - Wiley Evans; Katie Campbell; Carrie Weekes; Justin Del Bel Belluz; Jessy Barrette; Drew Jordison; Chris Mackenzie; Jonathan Bergshoeff; Carolyn Prentice; Rosie Savage; Isabelle Desmarais; Bryn Fedje; et al. (Scientific Reports)
Abstract Large changes in marine CO2 chemistry manifest in areas with weakly-buffered seawater where ocean acidification (OA) acts in concert with natural CO2 additions. These settings can exhibit periods of extreme OA in the form of multiple co-occurring stressors, including calcite undersaturation and low pH. Such conditions were observed in the northern Strait of Georgia, on the northeast Pacific coast, where extreme OA spanned a 3-year period. Here, we utilized an 8-year, highly-resolved record of seawater CO2 partial pressure and total dissolved inorganic carbon to decompose the drivers of this extreme OA. We find that variability in storm season intensity shaped the extent of conservative mixing and biogeochemical drivers such that manifests of extreme OA arise in this setting. Extreme OA manifested during years with weak storm seasons due to direct and indirect biogeochemical factors and the reduced impact of conservative mixing. This sensitivity to the storm season intensity highlights how vulnerable the northern Strait of Georgia is to subtle changes in environmental forcing and provides some predictive capacity for OA conditions over the coming year. These results illustrate that OA is not a “slow burn” process within weakly-buffered settings, but rather invokes periods of intensification with poorly understood biological implications.